Analysis of Image Interaction and Social Motivation in Virtual Communities: – Take the Example of Tiktok, Instagram Virtual Communities - Wang, Ke (Transactions on Social Science, Education and Humanities Research, 2024)
The purpose of this paper is to explore the relationship between image interaction and social motivation in virtual communities, and take Instagram and TikTok as case studies. First, the conceptual characteristics of virtual communities and the defined forms of image interaction are analysed, and then the classification of social motivation and its impact on user behaviour are explored, as well as the role of image interaction in shaping the social ecosystem, the social atmosphere and the user’s social network. In Instagram, image interaction behaviours were found to be positively correlated with user engagement, increasing users’ exposure and social influence. In TikTok, on the other hand, social identity based on image interaction was closely related to user satisfaction, promoting user loyalty and stickiness to the platform. In summary, image interaction, as an important form of social behaviour in virtual communities, has a positive impact on the development of the community and the social experience of users, but it also needs to pay attention to issues such as information security and content regulation.